2018
DOI: 10.1148/radiol.2018171756
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Contour-based Segmentation for 18F-FDG PET Imaging of Lung Tumors by Using ITK-SNAP: Comparison to Expert-based Segmentation

Abstract: Purpose To assess the performance of the ITK-SNAP software for fluorodeoxyglucose (FDG) positron emission tomography (PET) segmentation of complex-shaped lung tumors compared with an optimized, expert-based manual reference standard. Materials and Methods Seventy-six FDG PET images of thoracic lesions were retrospectively segmented by using ITK-SNAP software. Each tumor was manually segmented by six raters to generate an optimized reference standard by using the simultaneous truth and performance level estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Among the 110 stage III–IV LSCC patients enrolled in this retrospective study, seven patients with unqualified segmentation results and four patients with segmentation data unable to recognize were required to re-segment after the blind review, until qualified. Figure 2 describes the manual segmentation by using ITK-SNAP [ 32 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Among the 110 stage III–IV LSCC patients enrolled in this retrospective study, seven patients with unqualified segmentation results and four patients with segmentation data unable to recognize were required to re-segment after the blind review, until qualified. Figure 2 describes the manual segmentation by using ITK-SNAP [ 32 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, the dynamic PET data and the MR pre-contrast T 1 -mapping data were resampled to the 3D-T 1 space (libraries nilearn and nibabel), whereas the DCE data were motion-compensated (warping to the 3D-T 1 space) using the SyNQuicK procedure (library nipype, defaut parameters) implemented in Advanced Normalization Tools (ANTs) [ 38 , 39 ]. Tumor mask: the last frame of [18F]FDG-PET and DCE data, the pre-contrast T 1 -mapping data, and the post-contrast 3D-T 1 data were masked semi-automatically with ITK-SNAP ( http://www.itksnap.org ), which implements an active contour-based algorithm [ 40 , 41 ], as follows: an intensity-grading feature image was first computed to define the lesion boundaries by thresholding the intensities of the input image into the background and foreground (region competition approach, in which the intensity values ranged from − 1 to 1 for background and foreground respectively); one or more spherical seeds were then placed on the feature image to initialize the segmentation task; and the iterative algorithm was launched to propagate the seeds, driven by regularity constraints and the image intensity properties. The resulting PET, DCE, T 1 -mapping, and 3D-T 1 tumor masks were combined into a single multimodal tumor mask (library nilearn) using a basic intersection operation.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed mathematical insight into algorithms implemented in this software lies beyond the scope of current study and may be found in the paper by Yushkevich et al [15]. Although initially designed and tested for anatomical segmentation of brain structures, this segmentation technique has been validated both for other anatomical segmentation applications, e.g., for airway volume measurement on cone beam CT images by Almuzian et al [16] and for lung cancer metabolic volume segmentation on 18 F-FDG-PET imaging by Besson et al [17].…”
Section: Methodsmentioning
confidence: 99%